Postnatal Care Service Utilization among Mothers in Eastern Region of Nepal - Paudel, Ishwari Sharma; Bhattarai, Sailesh; Rayamajhi, Rajan Bikram; Parajuli, Surya Bahadur; Pokharel, Paras Kumar (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 62-67 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8808